2007
DOI: 10.1103/physrevlett.98.015002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ions in a Crossed-Field Diode

Abstract: The effect of ions in a magnetically insulated crossed-field gap is studied using a single particle orbit model, shear flow model, and particle-in-cell simulation. It is found that, in general, the presence of ions in a crossed-field gap always increases the electrons' excursion toward the anode region, regardless of the location of the ions. Thus, the rate at which the electrons migrate toward the anode, which is a measure of the diode closure rate, is related to the rate at which ions are introduced into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…In HPM devices, dense beam impact on the anode or collector surfaces leads to release of adsorbed gases 111,117 and ultimately plasma production that limit the achievable operating pulse length. 47,118 In compact mmw-to-THz high power sources, dense beam impact on the circuit or collector can lead to irreparable, single-shot damage, even with short pulses during initial device testing.…”
Section: Dense Beam Impact Physicsmentioning
confidence: 99%
“…In HPM devices, dense beam impact on the anode or collector surfaces leads to release of adsorbed gases 111,117 and ultimately plasma production that limit the achievable operating pulse length. 47,118 In compact mmw-to-THz high power sources, dense beam impact on the circuit or collector can lead to irreparable, single-shot damage, even with short pulses during initial device testing.…”
Section: Dense Beam Impact Physicsmentioning
confidence: 99%
“…We applied a −5000-V dc bias to the cathode while keeping the anode grounded; the cathode bias is ramped from 0 to −5000 V in 25 ns. All of these values were chosen to compare with [23]. The maximum number of particles for each species considered is 5 × 10 5 , and the number of physical particles per computer particle is 1 × 10 8 for pressures ranging from 1 × 10 −6 Torr to 1 × 10 −4 Torr.…”
Section: A Model Parametersmentioning
confidence: 99%
“…It has been shown that this can cause changes in the relativistic magnetron resonance condition which leads to pulse shortening and/or excitation of undesired modes [11], [18]- [22]. Furthermore, it has been conjectured that this electron migration results from the formation of an unintentional plasma in high-power crossed-field devices [11], [14]- [18], [22], [23]. The exact origin and role of these plasma ions have not been unambiguously determined [23].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations